2014
DOI: 10.1007/s12265-014-9595-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Balloon Inflation Pressure on Cell Viability with Single and Multi Lumen Catheters

Abstract: Infusion catheters, when used in combination with balloons, are subjected to pressure created by inflation of the balloon. The compression can reduce the catheter flow area and cause elevated shear stresses in the fluid. A model and experiments were developed with a range of applied balloon pressures to investigate whether such situations may cause cell lysis during stem-cell infusion through single-lumen catheters. It was found that for balloon inflation pressures in excess of ~7 atm, it is possible for cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…There, an illustration of the multi-lumen catheter is provided. This catheter is termed the ND ® Infusion Catheter which was also subject to prior published research [36][37][38].…”
Section: Methodsmentioning
confidence: 99%
“…There, an illustration of the multi-lumen catheter is provided. This catheter is termed the ND ® Infusion Catheter which was also subject to prior published research [36][37][38].…”
Section: Methodsmentioning
confidence: 99%
“…We did not consider the effects of the drill bit angle and geometry on the thermal necrosis of the artery wall vascular nerves during the DCP process. In previous studies, thermal stress has been investigated in a rotational atherectomy process, however, it is suggested that future studies should investigate mechanical impact on the blood (hemolysis) during this process [38].…”
Section: Limitationsmentioning
confidence: 99%
“…Dib et al [90] investigated the effect of balloon inflation on the viability of the infused cells, and suggested that multi-lumen catheters are superior. Behfar et al [91] modelled alternative needle designs to the conventional straight or helical needles with an end-hole.…”
Section: Strategies For Improving the Therapeutic Efficacy Of Cell Thmentioning
confidence: 99%